Destress 9-1-1—an online mindfulness-based intervention in reducing stress among emergency medical dispatchers: a randomised controlled trial. Issue 10 (28th May 2019) - Lilly, Michelle; Calhoun, Rebecca; Painter, Ian; Beaton, Randal; Stangenes, Scott; Revere, Debra; Baseman, Janet; Meischke, Hendrika
Abstract : Objectives: Emergency medical dispatchers (EMDs) experience significant stress in the workplace. Yet, interventions aimed at reducing work-related stress are difficult to implement due to the logistic challenges associated with the relatively unique EMD work environment. This investigation tested the efficacy of a 7-week online mindfulness-based intervention (MBI) tailored to the EMD workforce. Methods: Active-duty EMDs from the USA and Canada (n=323) were randomly assigned to an intervention or wait list control condition. Participants completed surveys of stress and mindfulness at baseline, post intervention, and 3 months follow-up. Repeated measures mixed effects models were used to assess changes in stress and mindfulness. Results: Differences between the intervention group and control group in pre–post changes in stress using the Calgary Symptoms of Stress Inventory were statistically significant, with a difference of −10.0 (95% CI: −14.9, −5.2, p<0.001) for change from baseline to post intervention, and a difference of −6.5 (95% CI: −11.9, −1.1, p=0.02) for change from baseline to 3 months follow-up. Change in mindfulness scores did not differ between groups. However, increases in mindfulness scores were correlated with greater reductions in stress for all participants, regardless of group (r=−0.53, p<0.001). Conclusions: Development of tailored online MBIs for employees working in challenging work environments offer a promising direction for prevention and intervention. This study found that a short, weekly online MBI for EMDs resulted in reductions in reports of stress. Implications of online MBIs in other emergency responding populations and directions for future research are discussed.